Toward Smart Governance: A Bibliometric Analysis of Digital Transformation in Public Administration - Zubaidah , Siti; Hermansyah, Hermansyah; Yansyah, Putra; Firdaus, Firdaus; Desiwantara, Desiwantara (Pencerah, 2025)
This study aims to explore the global research trends in digital transformation within the field of public administration through a bibliometric analysis. Utilizing Scopus-indexed literature, the study applies a systematic review of articles published in English and classified under the social sciences subject area. The data collection was conducted on July 2, 2024, at 14:25 WIB, using the keywords “digital transformation” and “public administration,” (TITLE -ABS-KEY (